Cytology and Genotyping of High-Risk Human Papilloma Virus from Female Sex Workers in Makassar - Juan1, Sharvianty Arifuddin2, Abdul Rahman3, St. Nur Asni1, Syahrul Rauf2, Masita Fujiko4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objective: This study aims to determine the results of cytological examination and genotype of high riskHPV in women work as femalesex workers (FSW)at Makassar, South Sulawesi.Method: This study designed as analytical study with a cross sectional analysis approach and samplecame from female sex workers in the Makassar city. Research was conducted in the localization area ofsex worker, and conducted from March 2019 - September 2019. The research sample consist of womenwith reproductive age who sex workers, and meet the inclusion criteria. The cytological examination wasperformed using the Thin Prep Pap Test and the DNA HPV detection (genotyping) using the reverse dot blot“flow through” hybridization method. Data were analyzed with SPSS.Results: Our study found that most of the FSWs who were sampled are > 30 years old (61.3%), had <9 yearsof education (66.3%), were married (77.5%), nulliparous (62.5%), being FSW> 1 year (86.3%), age at FSW? 15 years (73%), age at first coitus ?15 years (82.3%), number of sex partners within a month ?5 (61.3%),the last number of sexual partners in the last 1 month<5 (58.8%), did not have an Sexual TransmittedInfection (STI) (96.3%). The number of FSWs who using and not using condoms was comparable (50%each), and all samples had never vaccinated with HPV vaccine. It was found that based on the type of lesion,most FSW samples had non-specific and non-bacterial cervicitis (60%) and the remaining 40% had nolesions. Based on the distribution of HPV genotypes in commercial sex workers, most of the samples had ahigh risk HPV of 25%. Duration to be FSW connected with high risk HPV (p <0.05).Conclusion: There is a significant relationship between duration of being FSW and high risk HPV genotype.Our study highlited that FSWs who work for >1 year are prone to having high risk HPV.